Investigation on the current facilities for persons with disabilities in public universities / Farah Adiba Shamsuddin - Shamsuddin, Farah Adiba (Faculty of Architecture, Planning and Surveying, 2013)
The aim of this dissertation is to highlight the effectiveness of the existing facilities for the persons with disabilities in public universities while the objectives of this research is to review the effectiveness of existing facilities for the PWD provided in public universities, to reveal users perception on the effectiveness of facilities for the PWD in public universities, and finally to outline ways to improve the effectiveness of the facilities for the PWD in public universities. This research is expected to help the disabled students to enjoy the facilities for the PWD provided in public universities as much as other people enjoy the facilities being provided. Therefore, this research will indirectly helps to improve the quality of the facilities provided for the PWD in public universities. The methods used in collecting data are through interviews, questionnaires and observations. The questionnaires were distributed to 30 respondents of normal and disabled students. From the results, it is clear that the students feel that the facilities for the PWD provided still need to be improved. From the result, we know that although the facilities for the PWD are provided in public universities, the PWD still cannot move independently and need help from the normal students. Moreover, the existing facilities are not built according to the standards. Two major recommendations were made to the study which are firstly, the number of facilities for the PWD need to be increased in public universities and secondly, the existing facilities for the PWD need to be improved so that the disabled students can use the facilities efficiently.